Self-efficacy and quality of life in adults who stutter - Carter, Alice; Breen, Lauren; Yaruss, J.; Beilby, Janet (Elsevier, 2017)
Purpose: Self-efficacy has emerged as a potential predictor of quality of life for adults who stutter. Research has focused primarily on the positive relationship self-efficacy has to treatment outcomes, but little is known about the relationship between self-efficacy and quality of life for adults who stutter. The purpose of this mixed- methods study is to determine the predictive value of self-efficacy and its relationship to quality of life for adults who stutter. Method The Self-Efficacy Scale for Adult Stutterers and the Overall Assessment of the Speaker's Experience with Stuttering were administered to 39 adults who stutter, aged 18– 77. Percentage of syllables stuttered was calculated from a conversational speech sample as a measure of stuttered speech frequency. Qualitative interviews with semi-structured probes were conducted with 10 adults and analyzed using thematic analysis to explore the lived experience of adults who stutter. Results Self-efficacy emerged as a strong positive predictor of quality of life for adults living with a stuttered speech disorder. Stuttered speech frequency was a moderate negative predictor of self-efficacy. Major qualitative themes identified from the interviews with the participants were: encumbrance, self-concept, confidence, acceptance, life-long journey, treatment, and support. Conclusion Results provide clarity on the predictive value of self-efficacy and its relationship to quality of life and stuttered speech frequency. Findings highlight that the unique life experiences of adults who stutter require a multidimensional approach to the assessment and treatment of stuttered speech disorders.